New Prospects in Direct, Inverse and Control Problems for Evolution Equations - Favini, Angelo.; Favini, Angelo.; Fragnelli, Genni.; Fragnelli, Genni.; Mininni, Rosa Maria.; Mininni, Rosa Maria. (Springer INdAM Series,, 2014)
This book, based on a selection of talks given at a dedicated meeting in Cortona, Italy, in June 2013, shows the high degree of interaction between a number of fields related to applied sciences. Applied sciences consider situations in which the evolution of a given system over time is observed, and the related models can be formulated in terms of evolution equations (EEs). These equations have been studied intensively in theoretical research and are the source of an enormous number of applications. In this volume, particular attention is given to direct, inverse and control problems for EEs. The book provides an updated overview of the field, revealing its richness and vitality.